Perencanaan Pengembangan Industri Penutuhan Kapal (Ship Recycling) di Kabupaten Tanggamus, Lampung - Sanyoto Widagdo (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aimed to analyze the preparation of maritime industrian estate at Tanggamus, Lampung in support of ships recycling industrial development, and then to arrange the planning of ship recycling industry development with substantive planning and procedural planning analysis. Substantive planning analysis through the approach of PEST’s Plus (Political, Economic, Social, Technology, and Environment), while procedural planning analysis using TAIDA as the method of preparation of strategies to deal with any possible scenario. The method used in the form of qualitative descriptive. Based on cross-impact analysis and causal-loop analysis, it was found that the focal concern and the uncertainties came from political and economic variables. There are four scenarios generated from scenario-cross diagram, scenario A (Surge Forward), scenario B (Yaw), scenario C (Sway), and scenario D (Heave Down). Then they are formed new vision and new mission, also the implementation of appropriate strategies of that possible scenarios to achieve the goals.Keywords: “Ship recycling, scenario planning”